Dynamic Analysis of Geogrid-Reinforced Pavement under Area Load Configuration: A Numerical and Field-Based Study - Tiwari, Aanchal; Shahi, Padma Bahadur; Suwal, Rajan; Tiwari, Ram Chandra (Journal on Transportation System and Engineering, 2025)
This study examines the stress-strain behavior of flexible pavements reinforced with geogrids, specifically focusing on the mid-thickness of the base layer where reinforcement is applied. The issue addressed is the structural and surface distresses in flexible pavements, worsened by improper load distribution. The aim is to evaluate the effectiveness of geogrid reinforcement in reducing vertical deformation and improving overall pavement performance under varying load and drainage conditions. The scope of the study includes a comparative analysis of unreinforced and geogrid-reinforced pavement sections, using two vehicle types (TATA Truck Tipper SK 1613 and Ford Ranger Pickup) and speed 15 km/h, modeled under both constant and accelerated conditions. Field instrumentation, including earth pressure cells, strain gauges, and moisture sensors, was placed at two sections 100 meters apart on the Arughat-Okhale Road section of the Mid-Hill Road Project. A 3D Finite Element Modeling (FEM) analysis using PLAXIS was performed, validated with field-measured data. The analysis focused on compressive and tensile stress and strain at the subgrade and base layers, including comparisons between drained and undrained subgrade conditions. Results show that geogrid reinforcement reduces vertical deformation, with higher geogrid stiffness further improving pavement performance. Modeling the subgrade as undrained proved suitable for accurately capturing stress redistribution in regions with significant moisture fluctuation, and these results aligned with field observation data. This research highlights the role of geotextiles and geogrids as composite materials in pavement systems, demonstrating their combined impact on stress distribution, reinforcement efficiency, and performance. The findings contribute to the understanding of geogrid technology in mitigating structural and surface distresses in flexible pavements.